Effect of different concentration of maltodextrin and polyvinylpyrrolidone on stability of saffron’s effective compounds microencapsulated by spray drying - A. Kamali; P. Sharayei; R. Niazmand; S. Eynafshar (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2013)
The object of this study was to evaluate the influence of the different concentrations of wall materials (maltodextrin, MDX, dextrose equivalent 16.5-19.5 and polyvinylpyrrolidone, PVP40) on the microencapsulated effective compounds of saffron (crocin, picrocrocin and safranal) by means of spray  drying method. At the first step, the frozen dried aqueous extract of saffron’s effective compounds was prepared. Then, the solutions of 5, 10 and 15 percent of PVP and MDX containing 250 mg of freeze dried aqueous saffron extract were prepared. Afterwards, the prepared solutions were dried with spray dryer. At first the characteristics of microcapsules such as the color, aroma and flavor yield of microencapsulation, microstructure and particle size were tested, then the release speed of effective compounds at 52.89±0.22 humidity condition during 45 days of storage were evaluated. The results showed that the crocin content in microcapsules prepared with MDX, saffranal and picrocrocin content in microcapsules prepared with PVP were at the highest. The saffron’s effective compounds decreased with increasing wall concentrations. Microcapsules had spherical shape and nearly smooth surface and also microcapsules containing MDX as a wall material produced larger particles rather than microcapsules which were containing PVP.  In addition, PVP 5%- as a wall material- contained the most effective compounds of saffron after 45 days storage.